Finite Element Analysis of Steel Plates with Rectangular Openings Subjected to Axial Stress - Al-Yacouby, A.M. (MDPI, 2022)
Steel plates with openings are among the important ship structural components used in the shipâs hull to withstand the hydrostatic forces of the ocean, which cause sagging and hogging moments at the shipâs bottom. The existence of openings on plates can cause structural rupture, stress concentration and a decrease in ultimate strength. This research is aimed at investigating the influence of selected parameters on the ultimate capacity of steel plates with rectangular holes subjected to axial stress, using ANSYS finite element analysis (FEA) under its non-linear static structural programme. The main parameters investigated in this paper are the plate thickness, opening aspect ratio, number of openings, position of openings, and the boundary condition of the plate. The influence of these parameters on the stress of plates and their deformation was evaluated. The comparison of the numerical simulation with the well-established analytical method using the Navier solution and Roarkâs Formulas showed a good agreement. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.